The identity of Amomum trilobum and Amomum unifolium (Zingiberaceae: Alpinioideae), and description of four new related species from Vietnam - Leong-Škorničková, Jana; Đăng, Trần Hữu; Bình, Nguyễn Quốc; Hlavatá, Kristýna; Trường, Lưu Hồng; Đạt, Nguyễn Quốc; Trung, Nguyễn Thành; Newman, Mark (Phytotaxa, 2019)
The identities of Amomum trilobum and Amomum unifolium, described from material originating from uncertain location in Indochina, are discussed. A lectotype of Amomum unifolium is designated here and epitypes with complete flowers are designated to ensure unambiguous application of both names. In addition, four new related species are presented in this paper, Amomum cinnamomeum, A. corrugatum, A. lutescens and A. miriflorum. Detailed descriptions, colour plates including flower dissections, notes on habitat and preliminary IUCN assessments are given for all six species.